Non-Native EFL Lecturers’ Strategies in Building Their Pragmatics Competence - Leffi Noviyenty (UNIB Press, 2023)
This is a qualitative case study that focused on elaborating the strategies used by EFL lecturers in building their pragmatic competence, the benefit they got after using those strategies, and how the lecturers built up students’ pragmatic competence in the classroom. Interviews, observation, and document analysis were the techniques of collecting data. 7 English lecturers were selected as the subject of the research. The findings showed that the English lecturers used several strategies to build their pragmatic competence, namely watching western films, reading English novels, building communication with native speakers, and joining international friendship community. Those strategies enriched their vocabulary or choice of words and idioms and trained them to speak natural English in a variety of communication contexts. Students’ pragmatic competence was built by using films, top-down approach on pronunciation teaching, pair work speaking and small group discussion, using authentic language in meaningful context, providing corrective feedback, introducing fillers, conversation maintenance cues, and implementing responsive activities. Pragmatic competence should be a leading goal for all those who teach ESL/EFL language, which simultaneously represents a challenging task as well. Keywords: communication skills; English teachers; pragmatics competence